Prognostic role of plasma level of angiopoietin-1, angiopoietin-2, and vascular endothelial growth factor in hepatocellular carcinoma - Choi, Gwang Hyeon (World J Gastroenterol, 2021)
BACKGROUND: Most hepatocellular carcinomas (HCCs) are hypervascular, with characteristic features of hepatic arterial supply to the tumor. The factors involved in tumor angiogenesis include angiopoietin-1 (Ang-1), angiopoietin-2 (Ang-2), and vascular endothelial growth factor (VEGF). AIM: To investigate the profiles of plasma levels of angiogenesis markers in patients with HCC and evaluate their roles in predicting overall survival (OS) and progression-free survival (PFS). METHODS: Plasma samples from 240 prospectively enrolled HCC patients in the very early to advanced stages were used to measure the levels of Ang-1, Ang-2, and VEGF. Their associations with clinical characteristics, OS, and PFS were analyzed. RESULTS: The median plasma levels of Ang-1, Ang-2, and VEGF were 3216 pg/mL, 1684 pg/mL, and 26.5 pg/mL, respectively. The plasma level of Ang-2 showed a significant increase from early stage [Barcelona clinic liver cancer (BCLC) A] to intermediate (BCLC B) and advanced stage HCC (BCLC C/D), whereas Ang-1, VEGF, and alpha-fetoprotein (AFP) levels in the plasma did not show any such changes. Multivariable analysis, propensity score-matched analysis, and time-dependent receiver operating curve analysis revealed that Ang-2 levels had the highest predictive power for OS and PFS. Neither Ang-1 nor VEGF was significantly associated with OS or PFS. The neutrophil-to-lymphocyte ratio was an independent factor for OS and PFS. CONCLUSION: The plasma levels of Ang-2 correlated with liver function, tumor stage, and tumor invasiveness, showing better performance in predicting OS and PFS than AFP, Ang-1, or VEGF.